Design and Implementation of Animated Stickers as an Educational Tool for Adolescent Drug Awareness Using the MDLC Method - Nugroho, Aris Sarwo; Wibowo, Mars Caroline (International Journal of Graphic Design, 2024)
This study aims to design and implement animated stickers as an educational medium for drug abuse prevention using the Multimedia Development Life Cycle (MDLC) method. The MDLC process includes six phases: concept, design, material collection, development, testing, and distribution. In the concept phase, the educational goals and target audience are defined. The design phase involves creating visual sketches and animations using Adobe animate. In the material collection phase, relevant information about drug abuse is gathered from trusted sources. During the development phase, the animated stickers are created, incorporating visual and textual elements to convey anti-drug messages. The testing phase evaluates the effectiveness of the stickers using a survey of 100 adolescents aged 13-18 years. The results show a significant increase in understanding of drug abuse, with a 48% improvement in comprehension after exposure to the animated stickers, as measured by a Likert scale survey. The effectiveness was primarily evaluated based on user feedback regarding visual appeal, message clarity, and motivation to avoid drugs. The final phase involves distributing the animated stickers through social media platforms and messaging apps, targeting a broader audience. This study demonstrates that animated stickers are a highly effective tool for increasing drug awareness among young people